A Critical Discourse Analysis Of You C 1000 Audiovisual Ads In Shaping Indonesian Women’s Beauty Concept - Muftihaturrahmah Burhamzah; Lely Novia; Alamsyah Alamsyah (Universitas Negeri Makassar, 2021)
Abstrak.Health and beauty ads are one of the most ads of interest in Indonesia. Beauty is every woman's desire, and the concept of beauty in Indonesia has been changed from time to time. YOU C 1000 is a healthy drink contains 1000 mg of vitamin C that offers a different concept of beauty to the public, especially to Indonesian women. This study aims to analyze the way of YOU C 1000 audiovisual ads in shaping the Indonesian women beauty concept by using the Fairclough’s Critical Discourse Analyses (CDA) method. The findings of this study are divided into three dimensions of analysis, those are the microstructural (text), mesostructural (discourse), and macrostructural (sociocultural practices). It can be indicated from the ads that YOU C 1000 has been advertised by usingeasy-to-remember and catchy slogan, using Miss Universe as the powerful icon of women beauty, conveniently choosing the form of product to consume with a refreshing taste and packed in suitable packaging, using Indonesian images (its nature, culture, and people) and some of the Indonesian typical music in most of the ads, constantly articulating the product benefit and comparing it to other similar product, and also it is using some linguistic features that give strong opinion supported by general facts, and all of that ways is to deliver the ideology that beauty is start by being healthy inside and by that it will automatically radiate the true beauty outside and that one of the ways of being healthy is by consuming YOU C 1000 once a day regularly.